Disorders of lipid metabolism. Clinical Guidelines 2023 - M. V. Ezhov; V. V. Kukharchuk; I. V. Sergienko; A. S. Alieva; M. B. Antsiferov; A. A. Ansheles; G. G. Arabidze; D. M. Aronov; G. P. Arutyunov; N. M. Akhmedzhanov; T. V. Balakhonova; O. L. Barbarash; et al. (Российский кардиологический журнал)
The Russian Society of Cardiology (RKO)With the participation of: The National Society for the Study of Atherosclerosis (NOA), the Russian Association of Endocrinologists (RAE), the Russian Society of Cardiosomatic Rehabilitation and Secondary Prevention (RosOKR), the Russian Scientific Medical Society of Therapists (RNMOT), the Eurasian Association of Cardiologists, the Eurasian Association of Therapists (EAT), the Russian Association of Gerontologists and Geriatricians